Carbon Trading in Indonesian Based on Financial Services Authority Regulation Number 14 of 2023 Reviewed from Maqāṣid as-Syarī'ah and Green Economy - Elsa Febiola Aryanti; Hidayat Hidayat; Nurkhalis Muchtar (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Carbon trading is a strategic market instrument designed to reduce greenhouse gas (GHG) emissions in a measurable way. In Indonesia, this mechanism is regulated through Presidential Regulation No. 98 of 2021 and OJK Regulation (POJK) No. 14 of 2023. However, studies integrating ethical-religious aspects through Maqāṣid al-Sharī‘ah and the Green Economy paradigm remain limited. This research aims to analyze the integration of these two concepts within Indonesia's carbon trading system and evaluate the conformity of POJK No. 14 of 2023. The method employed is normative legal research with a qualitative content analysis approach. The findings indicate that: (1) carbon trading aligns with Maqāṣid al-Sharī‘ah in environmental protection (ḥifẓ al-bī’ah) through principles of justice and transparency; (2) carbon trading supports the Green Economy by internalizing environmental externalities into economic activities; and (3) POJK No. 14 of 2023 substantially accommodates Sharia values and sustainability. This integration serves as a vital foundation for a carbon trading system that is legally valid and provides spiritual and social benefits.